2008
DOI: 10.1186/1471-2164-9-286
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 90 Mb of the potato genome reveals conservation of gene structures and order with tomato but divergence in repetitive sequence composition

Abstract: Background: The Solanaceae family contains a number of important crop species including potato (Solanum tuberosum) which is grown for its underground storage organ known as a tuber. Albeit the 4 th most important food crop in the world, other than a collection of ~220,000 Expressed Sequence Tags, limited genomic sequence information is currently available for potato and advances in potato yield and nutrition content would be greatly assisted through access to a complete genome sequence. While morphologically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…The expected phenotypic mean values were calculated from the allele substitution effects as well as the bi-, tri-, and tetragenic interaction effects, which were calculated on the basis of the mixed-model described in materials and methods comprising both markers simultaneously. whole genome sequence of potato (Zhu et al 2008) (www.potatogenome.net) will facilitate further research on this topic.…”
Section: R3bmentioning
confidence: 99%
“…The expected phenotypic mean values were calculated from the allele substitution effects as well as the bi-, tri-, and tetragenic interaction effects, which were calculated on the basis of the mixed-model described in materials and methods comprising both markers simultaneously. whole genome sequence of potato (Zhu et al 2008) (www.potatogenome.net) will facilitate further research on this topic.…”
Section: R3bmentioning
confidence: 99%
“…Whereas, comparative mapping among close species by BAC-FISH does not rely on mapping group and polymorphism, and the effective fragments are larger, then the homologous or rearrangement found were greater. Therefore, based on the physical comparative mapping by using FISH, chromosome rearrangement and collinearity between Arabidopsis and Brassica (Howell et al, 2005;Ziolkowski and Sadowski, 2002), tomato and potato Szinay et al, 2008;Zhu et al, 2008), Oryza genus and Sorghum genus (Hass-Jacobus et al, 2006) were revealed, which provided information of systematic development and evolution research. In the present study, the corresponding locations between D genome and D subgenome as well as within D genomes indicated a conserved collinearity relationship.…”
Section: Comparative Analysis Of Bacs In Different Cottonmentioning
confidence: 99%
“…Several molecular marker-based genetic linkage maps of diploid potato were developed (Bonierbale et al 1988;Gebhardt et al 1989Gebhardt et al , 1991Tanksley et al 1992;Jacobs et al 1995), including a 10,000-marker ultradense map that represents one of the densest genetic maps in any eukaryote (van Os et al 2006). Other resources for genomics research have also been developed, including expressed sequence tags (ESTs) (Ronning et al 2003;Flinn et al 2005), bacterial artificial chromosome (BAC) libraries Zhang et al 2003;Chen et al 2004), and BAC end sequences (Zhu et al 2008). An international potato genome sequencing consortium has been established recently (http:/ /potatogenome.net) that will make potato one of few major crop species whose genome will be sequenced using a BAC-by-BAC-based approach.…”
mentioning
confidence: 99%